2016
DOI: 10.1103/physrevc.94.044619
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic effective reaction theory for deuteron-induced reactions

Abstract: The microscopic effective reaction theory is applied to deuteron-induced reactions. A reaction model-space characterized by a p + n + A three-body model is adopted, where A is the target nucleus, and the nucleon-target potential is described by a microscopic folding model based on an effective nucleon-nucleon interaction in nuclear medium and a one-body nuclear density of A. The three-body scattering wave function in the model space is obtained with the continuum-discretized coupled-channels method (CDCC), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 34 publications
2
20
0
1
Order By: Relevance
“…These energy dependencies of the measured f p BU are satisfactorily described by the empirical parametrization. The microscopic results at 25 MeV [15] show almost constant f p BU for the whole A interval analyzed, while at 56 MeV [14,15] show a steep decrease for target nuclei from A=12 up to A∼120, apart from the data, while for A>120 their underestimated values are obvious.…”
Section: Deuteron Breakupmentioning
confidence: 75%
See 3 more Smart Citations
“…These energy dependencies of the measured f p BU are satisfactorily described by the empirical parametrization. The microscopic results at 25 MeV [15] show almost constant f p BU for the whole A interval analyzed, while at 56 MeV [14,15] show a steep decrease for target nuclei from A=12 up to A∼120, apart from the data, while for A>120 their underestimated values are obvious.…”
Section: Deuteron Breakupmentioning
confidence: 75%
“…The comparison of the measured σ p BU at 15, 25.5, 56, 70, and 80 MeV deuteron energies and for target nuclei from 12 C to 232 Th [13], with (i) the above parametrization as well as the microscopic cross sections obtained in the frame of (ii) the CDCC extension of the eikonal reaction theory (ERT), using microscopic optical potentials by Neoh et al [14], and (iii) distorted wave Born approximation (DWBA) method with post form interaction and zero-range approach by Carlson et al [15], is shown in Fig. 3 (a-d).…”
Section: Deuteron Breakupmentioning
confidence: 99%
See 2 more Smart Citations
“…Зазначимо, що розглядаючи поле ядра-мішені лише кулонівським, інтеграл (10) можна отримати в аналітичному вигляді [3]. При одночасному врахуванні ядерної та кулонівської взаємодії амплітуду переходу (10) в аналітичному вигляді отримати доволі складно і тому при розрахунках необхідно використовувати наближені методи.…”
Section: теоретичний підхідunclassified